Komunikasi Interpersonal Pada Komunitas dalam Mencapai Aktualisasi Diri Orangtua tunggal Perempuan Dikala Pandemi - Elke Alexandrina; Prischa Nova; Chrisdina Chrisdina (Universitas Majalengka, 2021)
Being a single female parent is a challenge in itself. It is not uncommon for the stigma of society to underestimate or degrade women who are divorced or separated because they are not meant for each other or losing their spouse due to death. The condition of being a single parent who is required to be able to raise children and play a dual role sometimes presents its own problems. Social conditions that label widows make female single parent increasingly trapped in negative views. As social human beings, single parent also need self-actualization in order to be strong and empowered for their families. The presence of the Purple Women Community as a forum for single female parents is one way to shape the self-actualization of its members. Communication that goes through social media makes it easier for members to strengthen each other, share, and solve problems. During this pandemic, members communicate more often both in the form of conversations and attending various virtual seminars. Maslow divides the stages of human needs into 5 which lead to self-actualization. Through qualitative data that is strengthened by quantitative data, it is found that members of the Purple Women Community do feel that the communication that has been established helps the formation of self-actualization. Feeling comfortable in expressing their feelings and discussing both through forums and private channels using internet platforms occurs and forms self-actualization.